Cutting performance and tool wear of SiAlON and TiC-whisker-reinforced Si3N4 ceramic tools in side milling Inconel 718. Issue 3 (1st February 2022) - Ma, Zheng; Xu, Xingwei; Huang, Xianghui; Ming, Weiwei; An, Qinglong; Chen, Ming
Abstract: Cutting performance and tool wear of two ceramic tools, SiAlON and TiC-whisker-reinforced Si3 N4, in the side milling processes of Inconel 718 are evaluated in comparison, including cutting force, temperature, surface morphology, tool wear and corresponding mechanism. Results show that these two ceramic tools has advantages and disadvantages respectively, due to the properties of ceramic matrixes and the evolutions of build-up edges. SiAlON ceramic tool has better resistance to wear, but causes poor surface quality. TiC-whisker-reinforced Si3 N4 ceramic tool generates better surface quality, but bears severe wear. Brittle damage, as the main mode of wear, occurs to both ceramic tools in different formations. SiAlON ceramic tool is featured by crater-like damage on blades while TiC-whisker-reinforced Si3 N4 ceramic tool is featured by whole-layer damage on flank faces.